(untitled) (Journal of Laboratory Animal Science, 2024)
Animals are most often victimized during calamities and disasters such as flood, earthquake, epidemic, fire, protest and war. Prevention of animal suffering during such situations is the most challenging part to meet the animal welfare aspect. The recent pandemic caused by Covid 19 infection has brought the whole world to a standstill. The declaration of a public health emergency of international concern due to the SARS-CoV-2 outbreak in January 2020 and subsequently confirming the COVID-19 outbreak as a global pandemic by the World Health Organization (WHO) was a major global crisis in the history of human life. With the public health concern due to Covid-19 pandemic and rising number of cases, on 24th March 2020, the Hon Prime Minister of India declared a nationwide lockdown for 21 days and lockdown extended for two more times till June 2020. Several institutions associated with the day-to-day activities of the public were closed. It was a very difficult situation to arrange services for running the animal facilities in the research laboratories. This was the first-ever disaster when public services, transport and manpower availability were severely affected for the months. Although the husbandry practices in the established animal facilities in national laboratories/institutions/corporate were not affected severely during the Covid 19 pandemic, many small facilities in the zoology/pharmacy colleges and small establishments collapsed due to non-availability of manpower, bedding materials and feeds. Many research organizations were closed for daily working due to scarcity of the above services and allowed to work from the home wherever possible. To cope up with such a situation disaster management plan should be in place in all the animal facilities. We describe a disaster management plan for handling a similar situation if it arise in the future. The plan includes articulation of several authorities at different levels for the uninterrupted passage of services towards the arrangement of manpower, materials and feeds to avoid animal suffering.